Across Borders and Art Histories: Travelling Exhibitions - Świtek, Gabriela (Artium Quaestiones, 2024)
The concept of art geography is undergoing a process of revision in light of recent research on exhibition histories. The analysis of major perennial art exhibitions is conducted in relation to the spatial, global structures of social and economic life, or as an aspect of tourism geographies. The geography of art exhibitions entails mapping circulation, analysing the spatial and temporal conditions under which art is presented, and the identifying cultural boundaries in the reception of travelling artworks. This article examines the circulation of international exhibitions that were presented at the Central Bureau of Art Exhibitions (CBAE) in Warsaw as part of cultural diplomacy i the 1970s. During this decade, the CBAE gallery hosted exhibitions of contemporary art from twenty-one countries. What kind of foreign art was seen at the state-organised exhibitions in Warsaw depended on global geopolitics. The primary case study is the exhibition Contemporary Indian Art from the Collection of the National Gallery of Modern Art in New Delhi, which was toured from New Delhi through the Middle East to Eastern Europe (including Warsaw and Prague) in 1978–79. The exhibition brought together 100 works by 80 artists, created between the 1920s and 1970s. It included paintings by pioneers of modern and contemporary Indian art, such as Jamini Roy, Amrita Sher-Gil, Rabindranath Tagore, Gaganendranath Tagore, and K.C.S. Paniker. The diplomatic circumstances of organising the exhibition in Warsaw are set in the broader context of the Polish-Indian art exchange since the 1950s. This encompasses Poland’s participation in the New Delhi Triennial (established in 1968) and the completion of the modernist building of the Polish Embassy in New Delhi (1978). Furthermore, the article examines the impact of travelling national exhibitions on fostering intercultural understanding. The Contemporary Indian Art exhibition provided a valuable opportunity to transcend the conventional boundaries of Indian and Polish art histories. While in the 1960s and 1970s Polish academic discourse typically concluded the history of Indian art in the 1910s, the exhibition’s catalogue served as the primary source of information on twentieth-century Indian art. Consequently, the reception of Contemporary Indian Art in Warsaw is contextualised within the broader discourse of global art history and postcolonial studies.